96.2k views
4 votes
Rearrange the formula S = a (a - r) forr. A) r = a(S - 1) B) r = (S - 1) a C) r = a(S - 1) S D) r = a(S + 1) S

2 Answers

4 votes

Answer: C) r = a(S - 1) /S

Explanation:

User Tyl
by
5.1k points
0 votes

Answer: C)
r=a((S-1)/(S))

Explanation:

The given formula :
S=(a)/((a-r))

To rearrange the formula to find the formula for r , first we multiply both sides with (a-r), we get


(a-r)S=a

Divide both sides by S , we get


a-r=(a)/(S)

Subtract a on both sides , we get


-r=(a)/(S)-a\\\\ -r=a((1)/(S)-1)

Multiplying (-1) on both sides , we get


r=-a((1)/(S)-1)\\\\ r=a(1-(1)/(S))\\\\ r=a((S-1)/(S))

Hence, the correct answer is : C)
r=a((S-1)/(S))

User Israel Zalmanov
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.